Perancangan Sistem Informasi Pengolahan Data Gaji Karyawan Berbasis Web pada PT. Raksasa Indonesia - Siregar, Erlina; Muhathir, Muhathir (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2024)
Employees are work members who are owned by the company to help the company's work to be more improved. So that employees have the salary they get. This information system can help design an employee payroll data collection system that is still done manually so that it becomes website-oriented. The employee's salary is the salary that the employee is entitled to receive at the behest of the company owner. In collecting employee payroll data, it is necessary to pay more attention to detail. This is to avoid mistakes in data collection and losses to the company. In addition, in making monthly salary reports, the HRD or finance department must recap and separate employee salary data which is then inputted into a monthly salary report. The result of this design is a computerized web-based employee payroll information system. In the process of paying these employees, the finance department will record employee transactions in the transaction book and employees get proof of salary in the form of a piece of paper from finance. In addition, reports that will be submitted to HRD also still use a simple manual method, namely by printing all employee data based on their position.